Georgia Women Writers: A Narrative Study of Professional Georgia Women Writers to Determine Implications for Educational Change - Ragan-Martin, Wilma Maudrene Bronwyn (Valdosta State University, 2006)
By examining the lives of successful women writers from South Georgia, I have been able to discover patterns in their lives that encouraged these women to become writers. By using life story interviews and narrative inquiry, I was able to determine specific implications for educational change. These factors can be examined at school and at home to encourage both girls and boys to become more confident in their writing ability. In addition, all three writers gave generous suggestions to help with the teaching of writing. Three life story interviews of published women writers from South Georgia were completed. The transcripts were examined and analyzed in order to discover patterns in the lives of these women. Narrative inquiry was used to interpret the findings. Narrative inquiry was used as an extension of the life story interviews because it allowed a closer inspection of each participants story and gave another lens with which to analyze the data that was gathered. From this study, I learned that it is crucial that we encourage our students, both girls and boys, to write in every subject area, and that we allow them to write creatively and without the restraint of formulaic writing or the pressure to write perfectly the first time they attempt to create. Further, we must enable our teachers to become more comfortable with the teaching of writing, including exploring less traditional approaches to teaching and evaluating writing. Finally, and most importantly, we must encourage each and every student. Every one of the published authors interviewed noted the encouragement of a single teacher as critical to her choice to make writing a profession.
Chapter 1 INTRODUCTION . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 The Research Project . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 Problem Statement . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 Context of the Problem . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .2 Purpose of the Study . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .4 Research Questions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .4 Educational Implications . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .6 Conceptual Framework . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .7 Chapter 2 WRITING AND WOMEN WRITERS . . . . . . . . . . . . . . . . . . . . . . . .10 What Makes Writers Become Writers. . . . . . . . . . . . . . . . . . . . . . . . . 10 Womens Place . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .12 Chapter 3 METHODOLOGY . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .17 Research Design . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .17 Overview of the Study . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 18 Table 1: Data Planning Matrix . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 20 Emergent Design. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 20 Selection of Participants . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 21 Data Collection. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .22 Table 2: Contact with Authors . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 25 Data Analysis. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .25 Validity Issues. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 28 Conclusion Drawing and Verification. . . . . . . . . . . . . . . . . . . . . . . . . . 32 The Pilot Interview . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 33 Limitations of the Study. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .34 Chapter 4 LIFE STORIES. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 37 Amy Blackmarr. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 38 Tina Ansa. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 66 Janice Daugharty. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .122 Chapter 5 CROSS CASE ANALYSIS. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 131 Similarities. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .131 Differences. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .135 Addressing the Research Questions. . . . . . . . . . . . . . . . . . . . . . . . . . . .137 Emergent Themes and Other Findings. . . . . . . . . . . . . . . . . . . . . . . . . .143 a) Benefits of Writing. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .143 b) Self-Centered Personalities. . . . . . . . . . . . . . . . . . . . . . . . . .144 c) Isolation. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .144 Chapter 6 IMPLICATIONS FOR PRACTICE IN EDUCATION. . . . . . . . . . . . . 146 General Education Comments. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .146 Suggestions for the Teaching of Writing. . . . . . . . . . . . . . . . . . . . . . . . .148 Summary and Comments. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .164 Summary of Implications. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .165 Chapter 7 CONCLUSION. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 168 Benefits of the Study. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 168 Recommendations for Further Research. . . . . . . . . . . . . . . . . . . . . . . . . 169 Future Writing Handbook for Educators . . . . . . . . . . . . . . . . . . . . . . . . 171 REFERENCE LIST. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .173 APPENDIXES. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .180 A. Sample Interview Questions. . . . . . . . . . . . . . . . . . . . . . . . . 180 B. IRB Approval . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 183 C. Participant Informed Consent Forms. . . . . . . . . . . . . . . . . . .185 D. Sample MAXQDA Data File . . . . . . . . . . . . . . . . . . . . . . . . 187 E. Transcripts. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 189 F. Memos. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 281
Keywords: Women Writers in Georgia; Education; Educational change--United States; Women in literature